2023
DOI: 10.17221/162/2022-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of silver fir (Abies alba Mill.) and its comparison with Norway spruce (Picea abies L. H. Karst) from the same forest sites in the Czech Republic

Abstract: Forests in central Europe were affected by heavy bark beetle outbreak during the years 2014-2022. Decline of Norway spruce brought other species of forest trees, including the fir, to the fore. The nutritional level of silver fir is one of the studied topics. Needles in 14 Norway spruce (NS) -silver fir (SF) mixed forest stands from 4 regions in the Czech Republic have been sampled to survey their nutrition level. Nutrition of NS is often near or below the deficiency limit, while nutrition of SF was assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Its ameliorating effects were confirmed by recent studies (Podrázský et al 2018). It is also important that the roots of silver fir reach much deeper and are able to gain sufficient nutrients from the whole soil profile (Novotný 2023). Other studies showed, however, only a minor ameliorating effect of silver fir in comparison with Norway spruce.…”
mentioning
confidence: 62%
“…Its ameliorating effects were confirmed by recent studies (Podrázský et al 2018). It is also important that the roots of silver fir reach much deeper and are able to gain sufficient nutrients from the whole soil profile (Novotný 2023). Other studies showed, however, only a minor ameliorating effect of silver fir in comparison with Norway spruce.…”
mentioning
confidence: 62%
“…As with BG 132 -Rila, which is among the worst growing at both locations, the values in all monitored parameters for the Konratice location are higher than those at the Černovice location. Not only do climatic conditions have an effect on the successful growth of forest tree populations, but soil conditions and sufficient tree nutrition are also integral parts of the correct choice of locations for intended plantings (Novotný 2023;Podrázský et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently a clear decline of A. alba stands in Central European forests was reported (Novák and Kacálek, 2023). This is concluded to be determined not by a single inducing factor, but reflecting a more concerning behaviour of the species, and more specifically, its low resistance and low adaptability to different adverse environmental factors, that appear now days even within its natural distribution areas, and represent limitative circumstances.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 98%